Racism and Health-Related Quality of Life in Pediatric Sickle Cell Disease: Roles of Depression and Support. (29th May 2020) - Mougianis, Ifigenia; Cohen, Lindsey L; Martin, Sarah; Shneider, Caitlin; Bishop, Meredith
Abstract: Introductions: Sickle cell disease (SCD) is the most commonly inherited blood disorder in the United States, and it predominately affects the Black community. SCD is characterized by a number of symptoms, including unpredictable pain, which can lead to hospitalizations. Data indicate that people with SCD experience racism and ample data indicate that racism predicts depressive symptoms and impaired health-related quality of life (HRQOL). In contrast, research suggests that social support might buffer the impact of racism on depression. The aim of this study was to explore associations among perceived racism, depressive symptoms, and HRQOL in adolescents with SCD. Consistent with the literature, it was predicted that perceived racism would predict HRQOL through depression, and social support would moderate the negative impact of racism on depression. Methods: In a cross-sectional design, 75 inpatient adolescents with SCD completed measures of perceived racism, depressive symptoms, HRQOL, and social support. Results: This results indicated a moderated mediation model with greater perceived racism predicting more depressive symptoms, which in turn related to poorer HRQOL; greater access to social support from individuals with SCD strengthened the perceived racism—depressive symptom association. Conclusions: Findings suggest a model for how racism, depressive symptoms, HRQOL, and social support might interact in hospitalized adolescents with SCD. Longitudinal or experimental designs are needed to substantiate directionality among these variables. Results highlight several areas for future research and clinical avenues to improve the welfare of youth with SCD.